Engineered extracellular vesicles as therapeutics of degenerative orthopedic diseases - Wei, Junyu; Ou, Zixuan; Tong, Bide; Liao, Zhiwei; Yang, Cao (Frontiers in Bioengineering and Biotechnology, 2023)
Degenerative orthopedic diseases, as a global public health problem, have made serious negative impact on patients' quality of life and socio-economic burden. Traditional treatment methods, including chemical drugs and surgical treatment, have obvious side effects and unsatisfactory efficacy. Therefore, biological therapy has become the focus of research on degenerative orthopedic diseases. Extracellular vesicles (EVs), with superior properties of immunoregulatory, growth support, and drug delivery capabilities, have emerged as a new cell-free strategy for the treatment of many diseases, including degenerative orthopedic diseases. An increasing number of studies have shown that EVs can be engineered through cargo loading, surface modification, and chemical synthesis to improve efficiency, specificity, and safety. Herein, a comprehensive overview of recent advances in engineering strategies and applications of engineered EVs as well as related research in degenerative orthopedic diseases, including osteoarthritis (OA), osteoporosis (OP), intervertebral disc degeneration (IDD) and osteonecrosis of the femoral head (ONFH), is provided. In addition, we analyze the potential and challenges of applying engineered EVs to clinical practice.